Ethical Health Technology Assessment in Latin America: Lessons from Canada and Argentina - Martin, Carolina; Williams-Jones, Bryn; de Ortúzar, María Graciela (Acta Bioethica, 2011)
A wide array of biomedical and genetic technologies is becoming available in both developed and developing nations. This situation is the cause of growing concern for health policy makers who must evaluate the utility of these technologies for their inclusion in public health insurance programs. Ideally, policy makers would have the information necessary to rationally allocate scarce resources, prioritise technologies, and ensure fair access to necessary health care services. The reality, however, is that policy makers often do not have such information. In this paper, we argue that the field of Health Technology Assessment (HTA), through the integration of ethical analyses (i.e., an “ethical HTA”), can enable Argentinean and other Latin American policy makers to better understand the soco-ethical concerns raised by new biotechnologies.